Preliminary analysis on thermodynamic and thermo‐economic performance of a solar CPC–KCS hybrid system - Xiao, Lan; Fan, Ya‐Di; Wu, Shuang‐Ying; Chen, Zhi‐Li (Environmental progress & sustainable energy, 2019)
Using solar collectors to actuate Kalina cycle system (KCS) for electricity generation has been an attractive way to take advantage of solar energy. Most of the existing research is about KCS integrated with flat plate collector, evacuated tube collector, or concentrating collectors; however, little research focuses on the KCS powered by compound parabolic concentrator (CPC). Considering the merits of CPC, a Kalina 11 cycle system which is directly powered by CPC, named as solar CPC–KCS hybrid system is studied as the research object. Energy, exergy and thermo‐economic models are established to estimate the system performance by varying the solar radiation, evaporating temperature and concentration of working fluid. Results show that higher evaporating temperature improves thermal and exergy efficiency. There are optimal values of Te for maximum wnet, that is, Te,opt = 422.15, 434.15, and 446.15 K, respectively, at Xr = 0.95, 0.93, and 0.91; while Te,opt = 443.15, 437.15, and 425.15 K at Xb = 0.8, 0.7, and 0.6. Higher Xr and lower Xb is generally favorable for system performance. But when Te ≥ 422.15 K, lower Xb is not beneficial to ηex improvement anymore. Additionally, once evaporating temperature exceeds 439.15 K, it is cost‐effective to install a superheater to avoid erosion potential risk. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13135, 2019